Effects of exercise-based pulmonary rehabilitation on lung function, muscle strength and functional capacity in post-COVID-19 patients - Manzano, Roberta Munhoz; Heubel, Alessandro Domingues; Tanni, Suzana Erico [UNESP] (Springer Nature, 2024)
Purpose: To evaluate the effects of exercise-based pulmonary rehabilitation (PR) on lung function, muscle strength and functional performance in patients with post-COVID-19 symptoms. Methods: This is a quasi-experimental prospective study including 29 patients (aged 54 ± 11 years, 59% male) with post-COVID-19 persistent symptoms. Exercise training was performed during 6 weeks, twice a week, with each session consisting of aerobic, resistance, and inspiratory muscle training. Before and after exercise-based PR program, all patients were assessed for lung function, respiratory and peripheral muscle strength, and functional performance. Results: After exercise-based PR program, patients showed an improvement in lung function, including forced vital capacity, forced expiratory volume in one second, peak expiratory flow, and maximal voluntary ventilation (P < 0.05). Maximal respiratory pressures and upper limb muscle strength were increased (P < 0.05). Functional performance in timed up and go test, 1-min stair-climbing test, 1-min sit-to-stand test, and 6-min walk test were also improved (P < 0.05). Subgroup analyzes according to COVID-19 severity showed no significant difference in magnitude of response to the exercise-based PR program. Conclusion: Exercise-based PR improves lung function, respiratory and peripheral muscle strength, and functional performance in patients with persistent symptoms of COVID-19. These benefits were independent of disease severity.
Keywords: Exercise tolerance; Long-COVID-19; Lung function; Rehabilitation; Respiratory muscle training